2015
DOI: 10.1095/biolreprod.114.122887
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-Based Intrauterine Device Use Is Associated with a Thinner Apical Layer of the Human Ectocervical Epithelium and a Lower ZO-1 mRNA Expression1

Abstract: Currently, whether hormonal contraceptives affect male to female human immunodeficiency virus (HIV) transmission is being debated. In this study, we investigated whether the use of progesterone-based intrauterine devices (pIUDs) is associated with a thinning effect on the ectocervical squamous epithelium, down-regulation of epithelial junction proteins, and/or alteration of HIV target cell distribution in the human ectocervix. Ectocervical tissue biopsies from healthy premenopausal volunteers using pIUDs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
2
17
1
Order By: Relevance
“…ϩ T cell population differences during the menstrual cycle with increased levels during menstruation (51), while others did not find increased CD4 ϩ T cell numbers in cervical explant tissues collected from the luteal phase or in progesterone-based contraceptive users (10,50). Although cell populations were not assessed in our study, our data suggested that neutrophil and CD4 ϩ T cell signatures were associated with the luteal phase by GSEA.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…ϩ T cell population differences during the menstrual cycle with increased levels during menstruation (51), while others did not find increased CD4 ϩ T cell numbers in cervical explant tissues collected from the luteal phase or in progesterone-based contraceptive users (10,50). Although cell populations were not assessed in our study, our data suggested that neutrophil and CD4 ϩ T cell signatures were associated with the luteal phase by GSEA.…”
Section: Discussioncontrasting
confidence: 54%
“…This time of potentially increased epithelial barrier disruption may be a key feature contributing to HIV susceptibility since both in vivo macaque models and ex vivo human explant tissues show enhanced viral diffusion when the cellular junctions were compromised (16). Furthermore, the use of progesterone-based intrauterine devices has been associated with ectocervical epithelial thinning and decreased mRNA levels of important tight-junction proteins (50). This provides further evidence of the impact that progesterone levels can have on the physical barrier of the genital tract whether expressed endogenously during the luteal phase or through exogenous application.…”
Section: Discussionmentioning
confidence: 99%
“…A key feature of these observations was simplified in a multivariate model, which showed that DMPA users were clearly distinguished by an inverse relationship of increasing skin inflammatory proteins, including zonulin, with decreasing wound repair factors, such as trefoil factor 3, which may contribute to increased tissue permeability due to their known functions in tight junction disassembly and tissue repair . This is similar to observations at the mRNA level of where progesterone‐based intrauterine devices associate with ectocervical epithelial thinning and decreased tight junction transcripts . Therefore, progestin‐based hormonal contraceptives use alters inflammatory, barrier, and repair mechanisms in the cervicovaginal proteome, which may increase HIV susceptibility.…”
Section: Epithelial Barriersupporting
confidence: 82%
“…The results of our study highlight few changes in the lower genital tract inflammatory environment following Eng-Implant initiation. While several studies have evaluated genital tract immune changes after use of other hormonal contraceptive methods [17][18][19][20][21][22][23][48][49][50][51][52][53][54][55][56][57][58][59][60][61], to our knowledge, no published study has evaluated Eng-Implant. We report an increase in the proportion of CD4 T-cells expressing the co-receptor CCR5 at the genital mucosa with Eng-Implant use that could be associated with increased risk of HIV infection; however, not all our findings relate a clear picture of increased susceptibility.…”
Section: Discussionmentioning
confidence: 99%